Analyzing Grammatical Cohesion Devices in Pros and Cons Essays Written by Marine Science Students - Amrullah, Qadrina Lailyn; Ijabah, Nur; Auliya, Prativi Khilyatul; Ardiyansah, Tri Yuli; Batubara, Riska Widiyanita (Universitas Pahlawan Tuanku Tambusai, 2025)
In academic writing, cohesion plays a crucial role in creating clarity and flow. However, students often struggle to use cohesive devices effectively, which can impact the coherence of their writing. This study explores the use of grammatical cohesive devices in pros and cons essays written by students in the Marine Science study program to assess their effectiveness in conveying the writer’s intention. It aims to examine how these devices; references, substitution, ellipsis, and conjunction are employed to convey the writers’ intended meaning. Moreover, this study also identifies the most frequently used types of grammatical cohesive devices. Using qualitative content analysis approach, the researchers analyzed 80 essays to identify the frequency and effectiveness of each cohesive device. The findings reveal that reference (62.50%) was the most frequently used device, followed by conjunction (34.38%), while substitution and ellipsis were rarely employed (1.56% each). These results indicate that students primarily rely on pronouns, pointer words, and conjunctions to link ideas and maintain the flow of their arguments. This study highlights the need for more structured instruction and additional support to help students improve their use of cohesive devices. The results also contribute to the development of cohesion theory, particularly in the context of student writing, and suggest future research directions. Further exploration of underutilized devices like substitution and ellipsis, as well as the use of cohesive devices in other text types, could enhance understanding of student writing and inform teaching strategies to promote stronger cohesion and clarity in student essays.